CSV- and PD-PWM modulation based on the TMS320F2812 DSP: An alternative for implementation - Rodigheri, A.; Mussa, S.A.; Ramos A, R.; Ruiz-Caballero, D. (2009 35th Annual Conference of IEEE Industrial Electronics, 2009)
This paper presents the difficulties encountered and alternatives found in the implementation of algorithms based on CSV-PWM (Centered Space Vector PWM) and PD-PWM (Phase Disposition PWM), applied to three-phase multilevel inverters, using the TMS320F2812 DSP. Some limitations such as the number of available comparators, the absence of a level disposition or a phase disposition, and the adjustment possibilities, made this task challenging and required the development of new strategies to deal with these limitations.